Kebahagiaan Puasa Ramadan dalam Perspektif Aristoteles - Noval MY (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the happiness of Ramadan fasting from Aristotle's perspective. This study applies a qualitative approach using the library study method. The formal object of this research is Aristotle's philosophy while the material object is happiness through fasting in Ramadan. The results of the discussion in this study indicate that happiness can be obtained from misery, happiness is not the sum of favors. This research concludes that the ultimate goal of everything that is done by humans is happiness. Ramadan fasting is a mandatory worship that is carried out when the month of Ramadan comes. Ramadan fasting in Aristotle's perspective is a method to achieve happiness offered by Islam. Because in fasting one must feel the misery of his lust and after it is passed, he will get happiness. This study recommends organizations and institutions that have an attachment to philosophy and theology to conduct a study of Aristotle's philosophy regarding happiness.